A geophysical insight of the lithostratigraphic subsurface of Rodafnidia area (Lesbos Isl., Greece) - Alexopoulos, J.D.; Voulgaris, N.; Dilalos, S.; Mitsika, G.S.; Giannopoulos, I.K.; Gkosios, V; Galanidou, N. (AIMS Geosciences, 2023)
The study area of Rodafnidia on the island of Lesbos (Greece) is considered of archaeological interest, as Paleolithic stone tools have been recovered through excavation and collected from the ground surface in recent years. Geologically, the area is mostly covered by Quaternary post-alpine deposits and volcanic rocks. This paper presents the application of a local geophysical survey to determine the volume of the upper Quaternary deposits in which the Paleolithic artefacts can be found and the identification of their ignimbrite substrates. For this reason, the geoelectrical method was selected as the most appropriate for determining the lithostratigraphic subsurface layers. More specifically, a grid of twenty-one (21) Vertical Electrical Soundings (VES) along with an Electrical Resistivity Tomography (ERT) was carried out. The interpretation of the results of these surveys, in conjunction with the results of older excavation trenches, revealed that the Quaternary deposits have been investigated at depths ranging from 0.5 up to 28.5 meters. Furthermore, the lithological boundary of these post-alpine deposits and their underlying pyroclastic ignimbrite flow (with resistivity 24.0–58.0 Ohm.m) seem to dip to the north. The volume of the Quaternary layer is proposed as the maximum depth for archaeological investigation with high chances to recover more Paleolithic material.